2019
DOI: 10.1021/acs.jafc.9b04694
|View full text |Cite
|
Sign up to set email alerts
|

N-(1-Deoxy-d-xylulos-1-yl)-glutathione: A Maillard Reaction Intermediate Predominating in Aqueous Glutathione-Xylose Systems by Simultaneous Dehydration-Reaction

Abstract: The effect of simultaneous dehydration-reaction (SDR) on Amadori rearrangement product (ARP) N-(1-deoxy-d-xylulos-1-yl)-glutathione and its key degradation products, 3-deoxyxylosone (3-DX) and 1-deoxyxylosone (1-DX), were investigated in an aqueous glutathione-xylose (GSH-Xyl) system. The yield of ARP was increased to 67.98% by SDR compared with 8.44% by atmospheric thermal reaction at 80 °C. Reaction kinetics was applied to analyze the mechanism and characteristics of ARP formation and degradation under SDR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(80 citation statements)
references
References 44 publications
3
77
0
Order By: Relevance
“…32 The dehydration process could stimulate the k 1 or k 1 ′ in both reaction pathways, and this mechanism has been explained in our previous research on kinetics under the VDR system. 23,25 The formation of ARP and DPs follows a zero-order reaction in the VDR system. 23 In the present reaction model, the formation rate k 2 of dominating product ARP and its degradation rate k 4 were calculated to be 8.5 and 1.7 mmol/L min −1 without EGCG, while the formation rate k 2 ′ was 15.8 mmol/L min −1 and the degradation rate k 4 ′ was 0.9 mmol/L min −1 in the presence of EGCG.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The dehydration process could stimulate the k 1 or k 1 ′ in both reaction pathways, and this mechanism has been explained in our previous research on kinetics under the VDR system. 23,25 The formation of ARP and DPs follows a zero-order reaction in the VDR system. 23 In the present reaction model, the formation rate k 2 of dominating product ARP and its degradation rate k 4 were calculated to be 8.5 and 1.7 mmol/L min −1 without EGCG, while the formation rate k 2 ′ was 15.8 mmol/L min −1 and the degradation rate k 4 ′ was 0.9 mmol/L min −1 in the presence of EGCG.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our previous work revealed that the formation and degradation of ARP followed zero-order kinetics in VDR systems. 23 Thus, ARP or DP contents were described by c = c 0 − kt, where c is the concentration of ARP or DPs at time t (min), c 0 is the initial concentration, and k is the reaction rate constant (min −1 ). The activation energy E a (kJ/mol) was evaluated by means of the Arrhenius equation.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Cui et al proposed a combination of thermal controlled reaction and successive vacuum dehydration which could provide a synergistic effect and improved the yield of phenylalanine-xylose-ARP from 13.6% to 47.23% after 30 min of vacuum dehydration [ 29 ]. Such a yield improving method was also applied to various subsequent studies of the group, such as glycine-ribose-ARP (0.77% to 64.5%), glutathione-xylose-ARP (8.44% to 67.98%) and proline-glucose-ARP (3.63% to 69.15%) [ 14 , 30 , 34 ]. However, not all the system is suitable for controlled thermal dehydration coupled with vacuum dehydration.…”
Section: Traditional and Recent Advances In Preparationmentioning
confidence: 99%
“…The glutathione-glucose system produced less roasted and nutty aroma with the same quantity as the glutamic acid-cysteine-glycine-glucose system, resulting from a slower release of hydrogen sulfide and ammonia participating in the subsequent volatile formation [ 70 ]. Glutathione-xylose-ARP was produced with a high yield of 67.98% by simultaneous dehydration reaction and produced more ketones, alcohols, and mainly furans (caramel-like and sweet flavor) than the mixture of the ARPs of the three amino acid constituents [ 30 , 71 ]. Additionally, the glutathione-xylose-ARP produced a few sulfur-containing compounds while the mixture of cysteine-xylose-ARP and three amino acid ARP mixture generated a potent meaty flavor, supporting the aforementioned suggestions that cysteine-xylose-ARP is capable of forming meaty flavors and the process is strengthened by glycine addition, possibly split from glycine-xylose-ARP.…”
Section: Flavor Generationmentioning
confidence: 99%
“…S4 and S5). The Maillard reaction proceeded through a nucleophilic addition between the carbonyl group of the reducing sugar and the amino group of the amino acid to produce a Schiff base which rearranged to form an Amadori product, 47,[53][54][55][56] seen at m/z 440.0258 (C17H30NO12) (Figure 8). The reaction continued via decarboxylation and dehydration to yield products at m/z 396.0127 (C16H30NO10) and m/z 378.0646 (C16H28NO9) respectively.…”
Section: Characterization Of Reaction Productsmentioning
confidence: 99%